SOME CHALLENGES FOR ACCOUNTING EDUCATION. - Welsch, Glenn A. (The Accounting Review, 1964)
Accounting is a great profession being dedicated to integrity, independence, objectivity, high personal performance, and service. It tends to bring out the best in an individual. Since education is central to the accounting profession, as it is to all of the professions, accounting educators must give the educational aspects serious and continuing attention if they are to meet their responsibilities to the students and to the accounting profession generally. Within the context of a rapidly expanding social and economic complex, question has been raised as to whether accounting can meet an implicit challenge that will be ever-expanding. Hopefully, accounting will be commanded by highly educated men of vision and ingenuity, so that it will be transformed into an even greater force through expanding services. Accounting educators have a singular responsibility to both recognize and surmount the challenges facing accountancy and accounting education. These challenges have short and long-run implications, the latter clearly being more fundamental, and unfortunately less demanding at any given moment.